The Maastricht Treaty in a Thirty-year Perspective - Trócsányi, László (Maastricht 30: A Central European Perspective, 2025)
The Maastricht Treaty represents a crossroad and turning point in the evolution of the European integration. The current paper explores the main characteristics of the period before and after this turning point including the relations between the Member States and the judicial power in the European cooperation. It also gives insights into the fault lines and tensions of the institutional structures following the conclusion of the Maastricht Treaty. The paper explores the cornerstones of a harmonious European cooperation: the principle of subsidiarity, the consensus-seeking and the preservation of cultural diversity.Keywords: Maastricht Treaty, European Court of Justice, national constitutional and hight courts in the European cooperation, subsidiarity, diversity.